Cobalt Replacement in Unsaturated Polyester Resins; Going for Sustainable Composites. Issue 1 (23rd August 2013) - Jansen, Johan F.G.A.; Hilker, Iris; Kleuskens, Engelien; Hensen, Guido; Kraeger, Ivo; Posthumus, Willem; Bowman, Christopher N.; Horkay, Ferenc
Summary As alternative to cobalt based catalysts, various other catalysts based on manganese, iron and/or copper were developed for curing unsaturated polyesters in styrene with a hydroperoxide. This development is based on the simultaneous tuning of the redox chemistry taking place on the transition metal as well as on the ligand. From a mechanical point of view, based on DMA, these systems behave as drop‐ins. Employing these systems, unsaturated polyesters diluted in vinyl esters can also be cured. This makes cobalt‐free and styrene‐ free unsaturated polyesters possible.